Analisis tingkat inflasi di Indonesia Tahun 1998-2020 (pendekatan error correction model) - Martanto, Bayu; Tan, Syamsurijal; Syurya Hidayat, M. (Jurnal Paradigma Ekonomika, 2021)
Inflation is a macroeconomic problem that is of concern to many parties because unstable inflation has a negative impact on people's welfare. This study aims to estimate the factors that influence inflation in Indonesia for the period 1998 - 2020. The research method uses descriptive analysis by providing an overview of inflation, interest rates, exchange rates, household consumption, and GDP in Indonesia during 1998-2020. Quantitative analysis using Error Correction Model (ECM). This study uses secondary data from the Central Statistics Agency (BPS) and Bank Indonesia (BI). The results obtained indicate that all variables (interest rates, exchange rates, household consumption, and GDP) simultaneously have a significant effect on inflation, both in the long and short term. Based on the partial test results, the interest rate variable has a positive and significant impact on inflation in Indonesia both in the long and short time. The exchange rate variable partially has a negative and significant effect on inflation in Indonesia, both in the long and short term. Furthermore, the GDP variable partially has a positive and significant impact on inflation in a long time but is not substantial in the short term. Meanwhile, the household consumption variable partially has no significant effect on inflation in Indonesia during the 1998-2020 period. Â